Rural students do better in STPM result show gap with urban youngster narrow - Rajaendram, Rebecca (The Star, 2016)
PUTRAJAYA: Rural Sijil Tinggi Persekolahan Malaysia (STPM) candidates are catching up with their urban counterparts when it comes to cumulative grade point average (CGPA) scores.